Uso del silicio en la reducción de la incidencia del tizón tardío (phythophthora infestans) de la papa, en la provincia de Chimborazo. - Chango Infante, Ximena Elizabeth (2021)
Late blight is one of the diseases that affects potato crops, caused by phythophthora infestans, whose increased aggressiveness has led to an extensive search for control measures. The objective of this work consisted in evaluating the use of silicon in reducing the incidence of late blight of potatoes, here two varieties of potato were managed, and two sources of silicon in three doses, with a DBCA, to determine the relationship Between incidence and severity of the disease versus the production of total polyphenols in the plant, a linear regression analysis was used. As a result, the application of silicon in solid mixture with the fertilizer allows the reduction of the incidence of late blight, the TT Iniap Gabriela showed to be the most affected, with an incidence of 47.5%, while Iniap Gabriela with a high dose of silicate of calcium, which had an incidence of 30%. The TT Iniap Fripapa presented an incidence of 23.75%, compared to the least affected treatment. Iniap Fripapa with the application of calcium silicate in a high dose with a severity of 17.5%. The Iniap - Gabriela TT showed a severity of 55.00% differentiated from the Iniap - Gabriela treatment with a high dose of calcium silicate that presented a severity of 36.25%, while the severity in the Iniap - Fripapa TT was 28.75%, compared to the treatment Iniap - Fripapa was less affected with application of Si O2 in medium dose, which showed severity of 18.75%, the incidence and severity are related to the production of total polyphenols.